PENGARUH PROFITABILITAS, LEVERAGE, DAN FEE BASED INCOME TERHADAP EARNING PER SHARE PADA BANK UMUM SYARIAH DI INDONESIA - Karnila, Karnila; Fitri, Meutia (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2018)
The purpose of this study is to examine the effect of profitability, leverage, and fee based income foward to earning per share. Data used in this study is secondary data. Purposive sampling method is used to determine sample and the number of sample to axamine is 11. Number of observations are 44 islamic banking company which listed in Indonesia stock exchange from 2011 to 2014. Analysis method used are multiple linear regression by using SPSS 22. The study using profitability, leverage, and fee based income as independent variable, and earning per share as dependent variable. The result of this study shows that on F test, profitability, leverage, and fee based income to earning per share. On partial test T, profitability, leverage, and fee based income variable to earning per share